2005
DOI: 10.1128/iai.73.8.4934-4940.2005
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Immunity Provides Both Optimal Mucosal and Systemic Protection against a Mucosally Invasive, Intracellular Pathogen

Abstract: It has been hypothesized that optimal vaccine immunity against mucosally invasive, intracellular pathogens may require the induction of different types of immune responses in mucosal and systemic lymphoid tissues. Mucosal type 2/3 responses (producing interleukin-4 [IL-4], IL-6 and/or transforming growth factor ␤) could be necessary for optimal induction of protective secretory immunoglobulin A responses. On the other hand, systemic type 1 responses (including gamma interferon [IFN-␥], tumor necrosis factor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 37 publications
6
46
0
2
Order By: Relevance
“…Vaccination studies confirmed these observations by providing evidence that CD8 ϩ T cells are particularly important to the development of protective immunity in mice immunized with recombinant plasmid DNA, proteins, or viruses (6,19,25,31,37,43,60). In addition to CD8 ϩ T cells, CD4 ϩ Th1 cells also play a role in immunity against T. cruzi after vaccination with plasmid DNA or recombinant protein (19,30,60).…”
supporting
confidence: 60%
“…Vaccination studies confirmed these observations by providing evidence that CD8 ϩ T cells are particularly important to the development of protective immunity in mice immunized with recombinant plasmid DNA, proteins, or viruses (6,19,25,31,37,43,60). In addition to CD8 ϩ T cells, CD4 ϩ Th1 cells also play a role in immunity against T. cruzi after vaccination with plasmid DNA or recombinant protein (19,30,60).…”
supporting
confidence: 60%
“…This result should be interpreted with caution, however, because it would be impossible to attribute the high susceptibility of the IL-12/IL-23 (p40) KO mice only to a defect of specific CD8 ϩ T cells. The absence of this cytokine impairs a number of other immunological functions, including the expansion of Th1 CD4 ϩ T cells and NKT and NK cells, all of which actively participate during the immune response to T. cruzi infection (7,15,23,30,42).…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the immune responses induced by intranasal vaccination, we measured antigen-specific proliferative responses and IFN-␥ production. Briefly, two doses of recombinant TS or negative control phage 10 (NC) protein (50 g) adjuvanted with CpG 1826 (10 g) were administered intranasally to BALB/c mice 1 week apart, as previously described (10). One month after the final vaccination, mice were challenged via contamination of the ocular surface with 3 ϫ 10 5 CMT as described previously (8).…”
Section: Resultsmentioning
confidence: 99%
“…Six-to 8-week-old BALB/c mice were immunized intranasally twice, 1 week apart, with either 50 g recombinant trans-sialidase (TS) protein or 50 g phage 10 protein as a negative control (NC) and 10 g CpG 1826 as previously described (10). All preparations of recombinant TS and phage 10 protein contained less than 15 endotoxin units/mg of protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation